Transcriptome profiling of transcription factors in Ganoderma lucidum in response to methyl jasmonate - Xu, Xiaolan; Zhu, Fengli; Zhu, Yuxuan; Li, Yujie; Zhou, Hao; Chen, Shilin; Ruan, Junshan (Frontiers in Microbiology, 2022)
To screen for transcription factors (TFs) that involved in the biosynthetic pathway of ganoderma triterpenoids (GTs) in Ganoderma lucidum, the chemical composition was analyzed by UPLC/Q-TOF-MS/MS, and the transcriptomes of mycelium induced by MeJA (methyl jasmonate) at final concentrations of 200 and 300 μΜ were analyzed. The results showed that a total of 89 components were detected in mycelium, primordium and fruiting body. The total content of triterpenoids was the highest in primordium, followed by fruiting body and mycelium, and there were103 TFs in response to MeJA-induction including 95 upregulated and 8 downregulated genes. These TFs were divided into 22 families including C2H2 (15), TFII-related (12), HTH (9), fungal (8), bZIP (6), HMG (5), DADS (2), etc. And the expression level data of TFs in the mycelia, the primordia and the fruiting body were downloaded from the database to determine whether they played a significant regulatory role. The results show that the expression level of GL23559 (MADS), GL26472 (HTH) and GL3118 (HMG) showed a positive correlation with the GTs content, while that of GL25628 (fungal) and GL26980 (PHD) showed a negative correlation with the GTs content. Furthermore, the over expression of the Glmhr1 gene (GL25628) in Pichia pastoris GS115 indicated maybe it was a negative regulator of GT biosynthesis through decreasing the production of lanosterol. This study provided useful information for a better understanding of the complex regulatory network involved in GT biosynthesis and fungal growth in G. lucidum.